2008
DOI: 10.3201/eid1405.071260
|View full text |Cite
|
Sign up to set email alerts
|

Lakes as Source of Cholera Outbreaks, Democratic Republic of Congo

Abstract: We studied the epidemiology of cholera in Katanga and Eastern Kasai, in the Democratic Republic of Congo, by compiling a database including all cases recorded from 2000 through 2005. Results show that lakes were the sources of outbreaks and demonstrate the inadequacy of the strategy used to combat cholera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 6 publications
8
72
2
3
Order By: Relevance
“…The causative bacterium may be free-living in the environment, with environmental reservoirs well described in endemic regions in Asia [1]; the microorganism can live in both fresh- (inland lakes) [2, 3] and salt-water (coastal, estuarine areas) environments [1]. Illness tends to occur in seasonal patterns [46], with seasonality often associated with environmental parameters such as rainfall [7] and temperature [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The causative bacterium may be free-living in the environment, with environmental reservoirs well described in endemic regions in Asia [1]; the microorganism can live in both fresh- (inland lakes) [2, 3] and salt-water (coastal, estuarine areas) environments [1]. Illness tends to occur in seasonal patterns [46], with seasonality often associated with environmental parameters such as rainfall [7] and temperature [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The study sites are located in Katanga Province approximately 200 km east of Lubumbashi in a riverine and lakeland area with a high prevalence of childhood diarrhea and endemic cholera. 37,38 Two sites eligible for both rotavirus and cholera vaccine introduction were selected, one (Kasenga) being more urban than the other (Nkolé). Kasenga is a rural town situated on the riverside of the Luapula River, which forms the border with Zambia, and has eight quartiers with a total population of 27,000 persons, mainly ciBemba-speaking inhabitants living in an area of 10 km 2 .…”
Section: Methodsmentioning
confidence: 99%
“…18 Bathing and drinking lake water have been shown to be risk factors for disease in Lake Victoria and Lake Tanganyika, both East African lakes in which hyacinth is prevalent. [7][8][9][10][11] A study in western Democratic Republic of Congo found that cholera outbreaks were more likely to occur and persist near lakes and that individual cholera cases were more likely among people living closer to the lakes. 8 The experimental data along with the epidemiologic linkage of cholera to lakes suggest that hyacinth might act as a nidus for amplification and/or maintenance of a reservoir for V. cholerae that can lead to repeated infections among people drinking or swallowing lake water.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to lakes has been shown to be epidemiologically linked with cholera disease in several East African countries. [7][8][9] Many of the Great Lakes in East Africa have become colonized with an exotic plant, the water hyacinth ( Eichhornia crassipes ); it was first documented in Lake Victoria in 1988. 10,11 We explore the temporal association between water-hyacinth coverage on Lake Victoria and cholera incidence in the Kenyan province bordering the lake.…”
Section: Introductionmentioning
confidence: 99%